(untitled) (Bangladesh Agronomy Journal, 2025)
An experiment was conducted at Central Research Farm, BARI, Gazipur during Rabi season of 2021-22, 2022-23 & 2023-24 to develop a fertilizer recommendation for chilli with onion intercropping system. Six treatment combinations viz. T1= 100% RDCF of chilli + 0% RDCF of onion, T2= 100% RDCF of chilli +10% RDCF of onion, T3= 100% RDCF of chilli + 20% RDCF of onion, T4= 100% RDCF of chilli +30% RDCF of onion, T5= 100% RDCF of chilli +40% RDCF of onion and T6= 100% RDCF of chilli +50% RDCF of onion were tested. The experiment was laid out in randomized complete block design with 3 replications. Both chilli and onion significantly influenced by different treatment combinations. Significantly the highest yield of chilli (12.18 t ha-1) and onion (8.13 t ha-1) were obtained from T6 treatment (100% RDCF of chilli +50% RDCF of onion) which was statistically similar with T5 treatment (100% RDCF of chilli +40% RDCF of onion). Chilli equivalent yield (CYI) progressively increases with the increase of inorganic fertilizers. The results showed that T6 provided the highest CEY (21.93 t ha-1) followed by T5 (21.88 t ha-1). The highest net return (430005 Tk ha-1) as well as BCR (4.67) were obtained from T5 treatment (100% RDCF of chilli +40% RDCF of onion) whereas the lowest net return (364411 Tk. ha-1) as well as BCR (4.28) were observed in T1 treatment (100% RDCF of chilli + 0% RDCF of onion).Though T6 treatment gave higher yield over all the treatments yet it showed lower BCR compared to T5 treatment due to higher cost involvement for inorganic fertilizer. Bangladesh Agron. J. 2025, 28(1): 23-28